Pembinaan Bacaan Al-Qur'an dan Fiqih Salat Berjamaah bagi Siswa MDTA Yayasan Pendidikan Islam Al-Muttaqin di Kelurahan Tanjung Rejo Kecamatan Medan Sunggal - Angga Kurniawan; Juli Maini Sitepu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The Independent Community Service Program (KKN) of the Universitas Muhammadiyah Sumatera Utara at MDTA Yayasan Pendidikan Islam Al-Muttaqin, in Tanjung Rejo Village, Medan Sunggal District, was held from September 1–13, 2025, as a form of student dedication to strengthening religious education in the community. This program focuses on the development of Quranic reading and fiqh of congregational prayer, aiming to foster students' love for worship and deepen their understanding of Islamic teachings. The methods used include a participatory approach through Quran learning activities, practicing wudu, congregational prayer, and teaching the exemplary stories of the companions of the Prophet Muhammad Saw. In addition to religious guidance, social activities such as group exercise, mutual cooperation, and the commemoration of the Prophet Muhammad's birthday were also conducted to build harmonious relationships between students and the local community. The results of the activities show an improvement in students' religious abilities in Quranic reading and congregational prayer, as well as a deeper spiritual awareness. This KKN program is a concrete example of the synergy between education, da'wah, and community service in building students' character and faith in the MDTA Yayasan Pendidikan Islam Al-Muttaqin environment.